Branding Desa Kalanganyar sebagai Ekowisata Bahari di Kabupaten Sidoarjo - M. Andi Fikri; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2016)
This study aimed to describe the potential development of Kalanganyar Village as a marine ecotourism in Sidoarjo regency, and to describe the supporting and inhibiting factors in Kalanganyar Village as marine ecotourism in Sidoarjo regency. Qualitative methods in this study used an interaction model consisting of three activities: data reduction, data presentation, and conclusion. Data collection techniques was obtained by direct observation of the research location and interviews to visitors of marine tourism in Kalanganyar Village, Sedati Sub-district, Sidoarjo Regency. The results of this study showed that Kalanganyar Village had many tourism potential that can be developed, the outline of the potential, can be divided into two, namely: village potential and natural potential. Potential villages consist of culinary, community activity units and souvenirs. The natural potential consists of natural nuance, fishpond and fishery sunset. The existence of marine ecotourism in the village of Kalanganyar as an overall tourism attraction received a good perception assessment, but need to be followed up by indicators considered bad by the informants in order to improve the perception assessment of the visitors and could provide a more memorable tourist experience.